2022
DOI: 10.1039/d2ew00062h
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in pollutant controlling performance by modified aggregate structure in extensive green roof substrate layer

Abstract: Pollutants leaching and control of the extensive green roof (EGR) during rainfall events is crucial to its improvement and promotion, in which the substrate layer plays a key role. Adding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The additives were added in proportion to the total volume of the substrate mixture. Considering our previous studies 14 and ensuring the rational comparison, the addition ratio of the additives was set at 2%. Non-woven geotextiles were used in the filter layer to prevent outflow from the entraining substrate materials.…”
Section: Experimental Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…The additives were added in proportion to the total volume of the substrate mixture. Considering our previous studies 14 and ensuring the rational comparison, the addition ratio of the additives was set at 2%. Non-woven geotextiles were used in the filter layer to prevent outflow from the entraining substrate materials.…”
Section: Experimental Columnmentioning
confidence: 99%
“…Previously, we had studied the feasibility and effect of polyaluminum chloride (PAC) addition in the EGR substrate layer on the improvement of pollutant-controlling performance. 14 The results showed that the addition of 2% PAC could lead to stable aggregates in the substrate layer. Compared with the control group without PAC addition, the EGR experimental device with 2% PAC could significantly improve pollutant removal and load reduction rates of EGR for nitrate, total nitrogen, and total phosphorus.…”
Section: Introductionmentioning
confidence: 96%